Transformasi Praktik Angklung di Era Digital: Audio, Visual, dan Instrumen Virtual - Fahmi Insanul Kamil; Jaeni Bwastap; Yahfenel Evi Fussalam (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
This study is motivated by the increasing digitalization of traditional music, which has not been specifically examined in the context of Angklung, particularly regarding shifts in form, practice, and cultural meaning. The study aims to analyze the transformation of Angklung in digital practices through audio, visual, and virtual instrument formats. A qualitative descriptive-analytical method was employed through literature review and non-participatory observation of Angklung-related content across digital platforms. The analysis is grounded in cultural transformation theory and an interpretive approach inspired by Clifford Geertz. The findings reveal three main forms of digitalization: audio-based practices that expand musical distribution and arrangement, visual-based practices that reshape performance and collaboration, and virtual instrument development that represents Angklung within digital music production systems. These transformations indicate a shift from collective, place-based practices toward more flexible and technology-driven forms. This study contributes to the development of arts scholarship by positioning digitalization as a process of cultural transformation and reinterpretation in traditional music.